Information Adequacy in Histopathology Request Forms: A Milestone in Making a Communication Bridge Between Confusion and Clarity in Medical Diagnosis - Fariba ABBASI; Yasaman ASGHARI; Zahra NIAZKHANI (Federation of Turkish Pathology Societies, 2023)
Objective: Information contained in request forms for histopathological examinations plays a critical role in the microscopic interpretation of tissue changes. Despite its importance, studies have shown inadequacies in the information communicated by clinicians. This study aimed to determine how well the necessary information is provided on the histopathology request forms and to compare its variability among different departments of a hospital. Material and Method: A retrospective, 3-month, cross-sectional study was conducted to evaluate all consecutive histopathology request forms received from different departments of a tertiary, academic hospital for three months, regarding the documentation of 12 criteria. Results: None of the 2040 requests received had all the required items. Four items of specimen description, laboratory and imaging findings, and physician contact number were available only in less than 12.5% (range between 0.05 to 12.45%) of the requests. However, four other items of patient name and contact number, physician name, and anatomical site of the lesion were documented in more than 90%. The median number of the documented items was the highest in the surgery and orthopedics (9 items) and the lowest in the pulmonology department (7 items). Comparison between departments showed that the documentation of items in the surgery department were significantly better than that of the ENT, urology, and internal medicine departments (p<0.001). Also, the internal medicine department was significantly different from all other departments (p<0.001) except neurosurgery (p=0.88). Conclusion: Our results point out a serious gap in the adequacy of pathology request forms, especially clinical items. Given the implication of such information to ensure patient safety, further studies are recommended to evaluate the impact of educational and supportive computerized interventions such as clinician education and barcoding and specimen tracking systems to help fill in the required items completely.